Motivations for Corporate Social Responsibility (CSR) Disclosures in Recent Years - a Systematic Literature Review - Miaojia, Wang (2020)
This paper discussed what motivates CSR disclosures in recent years by adopting the systematic literature review on 52 journals from Accounting and General Management, Ethics and Social Responsibility from 2015 to 2020. Referencing to the three-stage systematic review framework of Tranfield, Denyer and Smart (2003), this paper conducted the systematic literature review through planning, conducting, and reporting stages. This paper extend the existing literature by linking theory and methodology characteristics with motivation themes identified. There were four motivation themes synthesized in the systematic literature review chapter, which include legitimacy concern, financial performance management, strategic management, as well as internal institutional factors, the identified themes were further generalized in the analysis chapter into strategic and responsive CSR concerns. As a result, the strategically motivated concerns including financial performance management, strategic management, as well as internal institutional factors are identified as the most frequently occurred motivation themes. Moreover, the stakeholder theory and the quantitative methodology were identified as the mostly backed theoretical framework and empirical tool.